Analisis Rantai Nilai Dan Efisiensi Pemasaran Beras di Kabupaten Lombok Barat - Wuryantoro Wuryantoro; Ayu Candra (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The measurement of added value in the rice distribution flow is a strategic approach that can be used to increase competitive advantage, where customer value can be increased by better understanding the relationship between producers, suppliers (suppliers) and customers. One of the regencies in NTB with abundant rice/rice production is West Lombok Regency.  Rice milling is one of the central points in the rice agroindustry and an institution that connects every actor in the post-harvest rice supply chain, starting from unhulled rice to producing rice as the main product. The purpose of this research is to identify and examine the rice value chain mechanism related to product flow, financial flow and information flow on rice commodity, as well as to analyze the efficiency of rice distribution channel. The results show that in the rice supply chain there has been a product flow, financial flow and information flow that flows between marketing actors or institutions, and is able to provide adequate profits for each actor involved in the rice supply chain. The results also show that in West Lombok Regency there are 3 patterns of marketing channels and overall the three rice marketing channels are efficient. This is indicated by the results of the calculation of the value of the marketing efficiency measurement, both the results of the analysis of the margin, efficiency index and price share, have met the efficient criteria.